Tradisi Khataman Al-Qur’an di Pondok Modern Al-Makkiyah Desa Rantau Api Kecamatan Tengah Ilir Kabupaten Tebo Provinsi Jambi (Studi Living Qur’an) - Dianda Ulhaq (Dinasti International Journal of Education Management And Social Science, 2023)
This study discusses the social phenomenon of the living Qur'an, namely khataman al-Qur'an at Al-Makkiyah Modern Islamic Boarding School, Rantau Api Village, Tengah Ilir District, Tebo Regency, Jambi Province. The letters that are read in the procession of completing the Qur'an are from the letter al-Dhuha to the letter al-Nas. This study examines the tradition of khataman Al-Qur'an at Pondok Modern Al-Makkiyah by using a qualitative approach, namely observing people in the environment, interacting with them, trying to understand their language and interpretation of the world around them and documentation. The results of this study indicate that this activity started from the completion of the Qur'an which was held by the command of the leader of the Al-Makkiyah Islamic Boarding School Ustadz Muhammda Rovicky at that time with the aim of also getting used to the memorization of the students so that they could memorize short letters. from surah al-Dhuha to al-Nas at that time so that it became a tradition of Islamic boarding schools. The process of Khataman al-Qur'an at the Al-Makkiyah Islamic Boarding School is a routine activity that is carried out every day after the Asr prayer until before the Maghrib prayer for the time, namely, 17:30 wib to 18:30 in the process it takes approximately one hour. Khataman al-Qur'an which was held at Al-Makkiyah Islamic Boarding School started from Surah Ad-Dhuha to Surah An-Nas. The spiritual effects of completing the Qur'an on students are: Feeling closer to Allah SWT, being patient in carrying out obedience to Allah, putting worship before the interests of the world (Zuhud) and feeling sufficient (Qana'ah) for what Allah has given.